2019
DOI: 10.21203/rs.2.11911/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROS as a Novel Indicator to Predict Anticancer Drug Efficacy

Abstract: Background Mitochondria are considered a primary intracellular site of reactive oxygen species (ROS) generation. Generally, cancer cells with mitochondrial genetic abnormalities (copy number change and mutations) have escalated ROS levels compared to normal cells. Since high levels of ROS can trigger apoptosis, treating cancer cells with low doses of mitochondria-targeting / ROS-stimulating agents may offer cancer-specific therapy. This study aimed to investigate how baseline ROS levels might influence cancer … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Baseline intracellular ROS levels were positively correlated with the resistance levels to both drugs in the cell lines ( Fig. 3a & b), con rming our previous observations [36]. Positive correlations between mtDNAcn and intracellular ROS, mitochondrial superoxide ( Fig.…”
Section: Positive Correlations Between Cellular and Genetic Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…Baseline intracellular ROS levels were positively correlated with the resistance levels to both drugs in the cell lines ( Fig. 3a & b), con rming our previous observations [36]. Positive correlations between mtDNAcn and intracellular ROS, mitochondrial superoxide ( Fig.…”
Section: Positive Correlations Between Cellular and Genetic Parameterssupporting
confidence: 89%
“…However, how speci c mtDNA variations in uence the e cacy of mitochondria-targeting/ROS-stimulating therapy remains unclear. Our previous data have shown that elevated baseline intracellular ROS levels among different cancer cell lines correlate positively with increased resistance towards cisplatin and dequalinium, both being ROS-stimulating drugs [36]. We hypothesised that certain mitochondrial genetic abnormalities, including variations and copy number (mtDNAcn) changes, could in uence intracellular ROS levels, and therefore be utilised as biomarkers to predict cancer cells' response to ROS-stimulating agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are involved in many cellular processes, such as cellular energy metabolism, cellular communication, differentiation and apoptosis 14 . Changes in mitochondrial structure lead to disruption of mitochondrial membrane potential, unstable electron transport reaction, resulting in excessive production of reactive oxygen species, activation of caspase cascade reaction, and initiation of apoptosis pathway 15,16 . Abnormal mitochondrial function is closely associated with the characteristics of cancer cells, such as enhanced anabolism, unlimited proliferation potential, insensitivity to anti‐growth signals, impaired apoptosis, and reduced autophagy 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of mitochondria‐targeted cations in anti‐cancer therapy has two advantages. One is that they have a synergistic killing effect and the other is that because of their higher membrane potential compared to those of mitochondria in normal cells, they preferentially enter mitochondrial cancer cells, which allows cations to selectively target cancer cells and accumulate faster in mitochondria 15,17,18 . Mitochondria mediate the apoptosis cascade and the dormancy of the apoptosis mechanism has been emphasized as a key factor for therapeutic resistance, recurrence, and poor prognosis in patients with malignant tumours such as GBM 19 .…”
Section: Introductionmentioning
confidence: 99%